Students' Listening Preferences and Perception In Using XReading Audiobook - Ramadhanty, Virlyana (RETAIN, 2022)
The aim of this study is to portray freshmen students’ listening preferences when using XReading audiobook and to describe students’ perception about the improvement of their English skills after using XReading audiobook for several months. This study used mixed method, both quantitative and qualitative to get sets of data. 80 freshmen students, who were also active users of XReading program, were involved as subject of the study. The data were gathered through the combination of close-ended and open-ended questionnaire followed by interview session for participants who did not give clear answer. The data from questionnaire were analyzed using descriptive quantitative while the data from interview were transcribed and analyzed qualitatively. The result shows that most students prefer to have reading-while-listening activity rather than only listening to audiobook. Students can also take advantages of some features provided in XReading audiobook. In addition, students have positive response about XReading audiobook because it has some benefits and is helpful to improve their English skills especially listening skill. Keywords: Listening preferences, Students Perception, XReading audiobook.